2016
DOI: 10.1016/s1473-3099(16)30134-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens, prejudice, and politics: the role of the global health community in the European refugee crisis

Abstract: Involuntary migration is a crucially important global challenge from an economic, social, and public health perspective. The number of displaced people reached an unprecedented level in 2015, at a total of 60 million worldwide, with more than 1 million crossing into Europe in the past year alone. Migrants and refugees are often perceived to carry a higher load of infectious diseases, despite no systematic association. We propose three important contributions that the global health community can make to help ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 11 publications
(9 reference statements)
2
41
0
2
Order By: Relevance
“…The preponderance of respiratory infections is consistent with recent studies in Belgium, Germany, and Switzerland [8, 15, 16]. More frequent respiratory diagnoses among new arrivals are likely attributable to conditions in Dresden’s reception centers, which often had open sleeping arrangements and minimal temperature control.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The preponderance of respiratory infections is consistent with recent studies in Belgium, Germany, and Switzerland [8, 15, 16]. More frequent respiratory diagnoses among new arrivals are likely attributable to conditions in Dresden’s reception centers, which often had open sleeping arrangements and minimal temperature control.…”
Section: Discussionsupporting
confidence: 84%
“…A 2014 review of non-communicable diseases (NCDs) among urban refugees in developing countries found the prevalence of NCDs amongst those from the Middle East ranged from 9 to 50% [7]. Another recent review noted that the prevalence of TB in Syria, the country of origin of most asylum seekers in Germany in 2015, was lower than that in several European Union countries [8]. A small pilot study of disease prevalence among youth asylum seekers in Germany found that over half had infections, nearly half of which were Helicobacter pylori [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is also the complexity of reintroduction of communicable disease in a disease-eradicated community, which can occur with a new influx of refugee migrants. Furthermore, environmental infrastructure and lifestyle play an important role in disease transmission [24]. Science is often biased by perception, created in part by media and other channels of risk communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is debatable with many factual sources contradicting this assertion [24]. This conception challenges government programs accepting refugees for resettlement, as refugee adoption may cause potential burden on contentious societal resources [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…European countries were very concerned about refugees bringing infectious diseases to their countries; however, evidence to corroborate these particular fears was missing [5]. Overall, the health problems of refugees and migrants are similar to those of the rest of the population ranging from accidental injuries, reproductive health issues, to chronic diseases.…”
Section: Introductionmentioning
confidence: 99%